Behavioral ecology of mating and colony founding in the grass-cutting ant, Acromyrmex balzani (Hymenoptera: Formicidae) - Fowler, Harold G. (My University, 1997)
The grass-cutting ant Acromyrmex balzani conducts nuptial flights at dusk, often during light rain. The daily timing of flights is invariant, but annual occurrence is dependent upon meterological conditions. Males form aggregations over shrubs or other prominent objects, into which females fly to be mated. These aggregation sites are used perennially. Sexual competition among males is intense, with an average of 4 males simultaneously competing for access to each female in a mating ball. Multiple matings of females are common. The male genetial capsule is detatched and retained in the female genetalia upon mating, and females remove these prior to flying to mate again. Females found colonies independently and are not claustral.
Keywords: Acromyrmex balzani; Behaviour; Colony founding; Haplometrosis; Mating; Sex-ratio; Sexual competition